Laser cooling of a semiconductor by 40 kelvin: an optical refrigerator based on cadmium sulfide nanoribbions - Xiong, Qihua (2013)
We have demonstrated the first net laser cooling of semiconductors using CdS nanoribbons (or nanobelts) in this work. This net cooling effect is found to be facilitated by resonant high order annihilation of longitudinal optical (LO) phonons due to a strong exciton-LO phonon Fröhlich interactions. Using a pumpprobe luminescence thermometry technique to measure the local temperature change, we have achieved as large as 40 K cooling temperature from room temperature pumped by a 514 nm laser while a 532 nm laser pumping led to a cooling of 20 K. At 100 K, only the 532 nm laser pumping can lead to a net cooling of around 15 K. Our work opens new directions to search laser cooling semiconductors and makes it feasible to achieve all solid-state cryocoolers based on semiconductors.